(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
In the present work, nanocomposites of polyvinyl pyrrolidone (PVP), carboxymethyl cellu- lose (CMC) and lead oxide nanoparticles (PbO2) have been prepared to use for gamma ray shielding applications. The nanocomposites have been prepared by casting technique. The lead oxide nanoparticles were added to the mixture of (PVP 55 wt.% and CMC 45 wt.%) with different concentrations are (0,1.5,3 and 4.5) wt.%. The D.C electrical conductivity and optical properties of nanocomposites were studied. The experimental results showed that the D.C electrical conductivity increases with increase the lead oxide nanoparticles concentrations. The absorbance and optical constants increase with the increase of PbO2 concentrations but the energy band gap decreases with the increase of PbO2 concentrations. The results of (polyvinyl pyrrolidone, carboxymethyl cellulose and lead oxide nanoparticles) nanocomposites application for gamma ray shielding showed that the (PVP-CMC-PbO2) nanocomposite have high linear attenuation coefficients for Cs-137 gamma ray sources.